Respiratory health effects and exposure to superabsorbent polymer and paper dust - an epidemiological study - Torén Kjell; Dahlman-Höglund Anna; Holm Mathias (BMC, 2011)
Abstract Background The primary aim of the present study was to investigate if exposure to dust from absorbent hygiene products containing superabsorbent polymer is related to symptoms from the airways and from the eyes. The secondary aim was to estimate the current exposure to superabsorbent polymer among production and maintenance workers in a plant producing hygiene products. Methods The cohort comprised 1043 workers of whom 689 were exposed to super absorbent polymer and 804 were exposed to paper dust (overlapping groups). There was 186 workers not exposed to either superabsorbent polymer or to paper dust They were investigated with a comprehensive questionnaire about exposure, asthma, rhinitis and symptoms from eyes and airways. The results were analyzed with logistic regression models adjusting for sex, age, atopy and smoking habits. An aerosol sampler equipped with a polytetrafluoroethylene filter with 1 μm pore size was used for personal samplings in order to measure inhalable dust and superabsorbent polymer. Results The prevalence of nasal crusts (OR 1.4, 95% CI 1.01-2.0) and nose-bleeding (OR 1.7, 95% CI 1.2-2.4) was increased among the paper dust exposed workers (adjusted for superabsorbent polymer exposure). There were no significant effects associated with exposure to superabsorbent polymer (adjusted for paper dust exposure). The average exposure to inhalable levels of total dust (paper dust) varied between 0.40 and 1.37 mg/m3. For superabsorbent polymer dust the average exposure varied between 0.02 and 0.81 mg/m3. Conclusions In conclusion, our study shows that workers manufacturing diapers in the hygiene industry have an increased prevalence of symptoms from the nose, especially nose-bleeding. There was no relation between exposure to superabsorbent polymer and symptoms from eyes, nose or respiratory tract, but exposure to paper dust was associated with nose-bleeding and nasal crusts. This group of workers had also a considerable exposure to superabsorbent polymer dust.